Inflammation and intracellular exposure of dolutegravir, darunavir, tenofovir and emtricitabine in people living with HIV. Issue 3 (11th October 2022) - Ferrara, Micol; Cusato, Jessica; Salvador, Elena; Trentalange, Alice; Alcantarini, Chiara; Trunfio, Mattia; Cannizzo, Elvira Stefania; Bono, Valeria; Nozza, Silvia; De Nicolò, Amedeo; Ianniello, Alice; De Vivo, Elisa; et al.
Abstract : Aims: Antiretroviral (ARV) therapy reduces inflammation and immune activation in people with HIV, but not down to the levels observed in people without HIV. Limited drug penetration within tissues has been argued as a potential mechanism of persistent inflammation. Data on the inflammation role on ARV plasma/intracellular (IC) pharmacokinetics (PK) through to expression of cytochrome P450 3A/membrane transporters are limited. The aim of this study was to investigate the correlation between inflammation markers (IM) and plasma/IC PK of ARV regimen in HIV‐positive patients. Methods: We included ART‐experienced patients switching to three different ARV regimens. Plasma and IC ARV drug concentration means at the end of dosing interval (T0 ), IM on samples concomitantly with ARV PK determination: sCD14, CRP, IL‐6 and LPS were analysed. Results: Plasma and IC drug concentrations were measured in 60 samples. No significative differences between CRP, sCD14, IL‐6 and LPS values in the three arms were observed. A significant inverse correlation between tenofovir plasma concentration and sCD14 (rho = −0.79, P  < .001), and between DRV IC/plasma ratio and Log10 IL‐6 concentrations (rho = −0.36, P  = .040), and a borderline statistically significant positive trend between DRV plasma concentration and sCD14 (rho = 0.31, P  = .070) were suggested. Furthermore, a borderline statistically significant inverse trend between DTG IC concentrations and sCD14 (rho = −0.34, P  = .090) was observed in 24 patients on DTG‐based triple therapy. Conclusions: Our preliminary data support the hypothesis of lower DRV and DTG IC concentrations and lower TFV plasma exposure in patients with higher plasma IM suggesting an interplay between HIV drug penetration and persistent inflammation in cART‐treated HIV‐positive patients.